2019
DOI: 10.1515/hf-2019-0133
|View full text |Cite
|
Sign up to set email alerts
|

Investigating tool engagement in groundwood pulping: finite element modelling and in-situ observations at the microscale

Abstract: With industrial groundwood pulping processes relying on carefully designed grit surfaces being developed for commercial use, it is increasingly important to understand the mechanisms occurring in the contact between wood and tool. We present a methodology to experimentally and numerically analyse the effect of different tool geometries on the groundwood pulping defibration process. Using a combination of high-resolution experimental and numerical methods, including finite element (FE) models, digital volume co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Global DVC was utilized to assess swelling of spruce wood from dry to wet humidity states with 27 µm elements [26]. Indentation tests on Norway spruce were also studied with such approach with elements of the order of 130 µm in length [27]. To the best of the authors' knowledge, no in situ torsion test has so far been reported for wood.…”
Section: Introductionmentioning
confidence: 99%
“…Global DVC was utilized to assess swelling of spruce wood from dry to wet humidity states with 27 µm elements [26]. Indentation tests on Norway spruce were also studied with such approach with elements of the order of 130 µm in length [27]. To the best of the authors' knowledge, no in situ torsion test has so far been reported for wood.…”
Section: Introductionmentioning
confidence: 99%
“…Best wood species can then be chosen according to mechanical stability for a certain application. Wood-based composite production processes can be optimized 18 , 19 . New, more damage resistant wood-based products with better performance and improved durability can be designed 20 .…”
Section: Introductionmentioning
confidence: 99%